Perbandingan Model Pembelajaran Inkuiri dengan Model Pembelajaran Kooperatif terhadap Keterampilan Servis Atas Bola Voli - Andriana, Arief; Marlina, Rina; Julianti, Rekha Ratri (Journal of Sport Science and Education, 2021)
The study aims to compare two study models, both inquiry and cooperative models, to learn of a more significant impact on volleyball service skills. The study used experimental methods with sampling using cluster random sampling technique in class VIII two classes were randomly selected as samples, use design factorial 2x2. The data-analysis technique uses tests from tests and kai squared, which is the data analysis technique used to compare the two learning models used. Research obtained results ie 8,81>7,28. From the research results, it can be concluded that the cooperative learning model is better than the inquiry learning model.